Desarrollo Y Simulación De Un Modelo De Transceptor Basado En Prime Para Simulación Sobre Canal PLC - Veglia, Jorge E.; Martinez, David L. La Red; Scappini, Reinaldo J.R. (European Scientific Journal, ESJ, 2018)
The choice of modification technique for a communications system depends to a large extent on the nature and characteristics of the medium in which it must operate (Hrasnica et al., 2005). In a PLC (Power Line Communications) system, the first applications in the LDR band (oriented to the control of devices) operated with monocarrier modulations, such as ASK, BPSK, and FSK. This allows for low implementation costs, provided that it operates at low data rates and with an error correction system. It is clear that applications require a higher data rate. The modulation technique must overcome challenges such as the necessary equalization for the cause of the non-linearity of the channel, or avoid the propagation delays and the multipath caused by the impedance differences in the branches. Likewise, it must offer flexibility and avoid the use of certain frequencies if they are altered or assigned to another service and, therefore, cannot be used in PLC. In this scenario, one of the techniques that have been imposed in the most used developments in NB-PLC as in BB-PLC has been Orthogonal Frequency Division Multiplexing (OFDM). One of its most attractive aspects from the point of view of its complexity is the possibility of implementing the structure of its multifrequency modulation and demodulation scheme through a simple Inverse Discrete Fourier Transform (IDFT) and its corresponding direct transform, Fast Fourier Transform (FFT). Based on this technique, an appropriate transceiver scheme for operating on a PLC channel model was presented. This development implements the error correction technique proposed for NB-PLC.